(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzed the development of the travelogue genre, its origin, and its characteristics as a genre. The travelogue genre in Jadid literature was analyzed based on the works of Mahmudhoja Behbudi, Abdulla Avloni, Munavvar Qori, Abdurauf Fitrat and Abdulhamid Sulayman son Cholpon.